2013
DOI: 10.1177/0954405413486635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ti6Al4V machining forces and tool life for cryogenic versus conventional cooling

Abstract: The benefits of cryogenic cooling by liquid nitrogen in cutting of titanium alloys have often been evaluated as a comparison\ud to dry machining conditions. However, it is more interesting to quantitatively assess the performance of cryogenic\ud conditioning of the process with respect to standard industrial conditions, that is, with respect to flood emulsion cooling.\ud The technical and scientific literature is scarce and somehow contradictory, especially in terms of cutting forces and\ud coefficient of fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 18 publications
(2 reference statements)
4
27
0
1
Order By: Relevance
“…Furthermore, they noticed that cryogenic cooling improves dynamic recrystallisation and prevents grain growth within the material whilst increasing the surface and subsurface microhardness of the machined material. Strano et al (2013) empirically studied the effects of cryogenic cooling on cutting forces and tool wear in CNC turning of Ti-6Al-4V using a multilayer TiAlN-AlCrO coated tungsten carbide tool. They (Strano et al, 2013) reported that cryogenic cooling reduced the growth rate of flank wear resulting in 38.8% increased tool life as compared to flood cooling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they noticed that cryogenic cooling improves dynamic recrystallisation and prevents grain growth within the material whilst increasing the surface and subsurface microhardness of the machined material. Strano et al (2013) empirically studied the effects of cryogenic cooling on cutting forces and tool wear in CNC turning of Ti-6Al-4V using a multilayer TiAlN-AlCrO coated tungsten carbide tool. They (Strano et al, 2013) reported that cryogenic cooling reduced the growth rate of flank wear resulting in 38.8% increased tool life as compared to flood cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Strano et al (2013) empirically studied the effects of cryogenic cooling on cutting forces and tool wear in CNC turning of Ti-6Al-4V using a multilayer TiAlN-AlCrO coated tungsten carbide tool. They (Strano et al, 2013) reported that cryogenic cooling reduced the growth rate of flank wear resulting in 38.8% increased tool life as compared to flood cooling. Furthermore, the study revealed that cryogenic cooling reduced various components of cutting forces by 4% to11% in comparison with flood cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The flow rate reduction in this study was enabled through the evolution in the delivery line design. [23] Matteo Strano et al [25] has confirmed in his research that cryogenic machining is able to increase the tool life, even with respect to wet cutting. Besides, the results showed that not only cutting forces are reduced but also a small, albeit significant, reduction can be achieved in the coefficient of friction at the tool-workpiece interface.…”
Section: Novel Machining Techniquesmentioning
confidence: 91%
“…Better Ra with coolant is because coolant also serves as a lubricant between sliding surfaces (Dhar and Kamruzzaman, 2007). Another fact is the substantial alteration of coefficient of friction at the tool-work interface in the presence of a coolant (Strano et al, 2013). The aggravated tool wear under dry (no-coolant/lubricant) condition also increases the Ra and counteracts against the thermal softening gain.…”
Section: Effects On Surface Roughnessmentioning
confidence: 99%